Acute appendicitis caused by Echinococcus granulosus: report of a case and literature review - Vera-Portilla, Angel F. (2020)
Acute appendicitis is the most frequent surgical emergency instance in young adults; and its association with parasitic infections is rare. Of these particular cases, appendix location of hydatid cyst is extremely rare; and there have been published reports of such cases only in Iran, India, Tunisia, and Peru. We present the case of a 52-year old male subject born in Puno, with no relevant past medical history, who was admitted with a clinical condition typically consistent with acute appendicitis. When this patient underwent surgery, the appendix was found showing a cystic mass, compatible with complicated Echinococcus granulosus hydatid cyst. Later on, three additional intraabdominal hydatid cysts were identified. There was no surgical or trauma past history, so it was concluded this condition corresponded to disseminated primary intraabdominal location of hydatid disease, including the appendix, liver, and peritoneum.